Intellectual Property and Theories of Justice
XI, 277 p.
Keywords: Fourteen philosophers, economists and legal scholars address the question 'Can intellectual property rights be fair?' What differentiates intellectual from real property? Should libertarians or Rawlsians defend IP rights? What's wrong with free-riding? How can incentives be taken into account by theories of justice?